MORAL DELIBERATION BY NURSES AND MEMBERS OF THE ASSISTENTIAL ETHICS COMMITTEE IN A CLINIC OF MAGALLANES, CHILE - Barrientos, Mireya Inés Triviños; Schneider, Dulcinéia Ghizoni; Alarcon Bustos, Elide Mariela (My University, 2020)
ABSTRACT Objective: to know how the nurses working in the Critical Care Unit for adults and the members of the Assistential Ethics Committee deliberate on the assistential ethical issues in a Clinic of Magallanes, Chile. Method: a qualitative research of an exploratory and descriptive character conducted in a Clinic of Magallanes, Chile. Data collection was performed by means of a semi-structured interview in the period from March to May 2018, with ten nurses working in the Critical Care Unit for adults and with four members of the Assistential Ethics Committee who were clinical professionals in different disciplines. The statements obtained were organized in Atlas.ti and analyzed in the light of the theoretical reference framework of ethics, of principalist bioethics, and of Diego Gracia's moral deliberative method. Results: the two professional teams that participated in the research showed having ethical values and principles: protection of human dignity; respect for the patients' rights in all scopes, contexts, and interventions, targeted to provide humanized clinical practices based on scientific evidence and in safeguarding the protection and fulfillment of the patients' rights. Conclusion: nurses show knowledge, empathy, and moral sensitivity when conducting the moral deliberative model in assistential problems. The members of the Assistential Ethics Committee deliberate as a team and come to an agreed upon conclusion, always thinking in the best respect and benefit for the patient's well-being, with empathy and prudence in decision-making as references.
Keywords: ethics; bioethics; ethics nursing; moral deliberative method; nursing care